Xanthine Oxidoreductase Is Involved in Chondrocyte Mineralization and Expressed in Osteoarthritic Damaged Cartilage - Nasi, Sonia; Castelblanco, Mariela; Chobaz, Véronique; Ehirchiou, Driss; So, Alexander; Bernabei, Ilaria; Kusano, Teruo; Nishino, Takeshi; Okamoto, Ken; Busso, Nathalie (Frontiers in Cell and Developmental Biology, 2021)
Pathologic calcification of cartilage consists of the formation of basic calcium phosphate (BCP) and/or calcium pyrophosphate dihydrate (CPPD) containing calcium crystals in mature hyaline or articular cartilage and is associated with ageing, cartilage injury and likely plays a role in accelerating the pathology of osteoarthritis (OA). The pathways regulating joint calcification, in particular cartilage calcification, are not completely understood, but inflammation and the formation of reactive oxygen species (ROS) are contributory factors. The xanthine oxidase (XO) form of Xanthine oxidoreductase (XOR), the key enzyme in xanthine and uric acid metabolism, is a major cellular source of superoxide. We hypothesized that XOR could be implicated in chondrocyte mineralization and cartilage calcification and degradation in OA. We showed both in murine primary chondrocyte and chondrogenic ATDC5 cells, that mineralization was inhibited by two different XOR inhibitors, febuxostat and allopurinol. In addition, XOR inhibition reduced the expression of the pro-mineralizing cytokine IL-6. We next generated XOR knock-out chondrocyte cell lines with undetectable XOR expression and XO activity. XOR knock-out chondrocyte cells showed decreased mineralization and reduced alkaline phosphatase (Alp) activity. To assess the precise form of XOR involved, primary chondrocytes of XOR mutant mice expressing either the XDH form (XDH ki) or the XO form (XO ki) were studied. We found that XO ki chondrocytes exhibited increased mineralization compared to XDH ki chondrocytes, and this was associated with enhanced Alp activity, reactive oxygen species generation (ROS) and IL-6 secretion. Finally, we found increased XOR expression in damaged vs. undamaged cartilage obtained from OA patients and XOR expression partially co-localized with areas showing pathologic calcification. Altogether, our results suggest that XOR, via its XO form, contribute to chondrocyte mineralization and pathological calcification in OA cartilage.